Risk of rapid global functional decline in elderly patients with severe cerebral age-related white matter changes: the LADIS study - Inzitari, Domenico; Simoni, Michela; Pracucci, Giovanni; Poggesi, Anna; Basile, Anna Maria; Chabriat, Hugues; Erkinjuntti, Timo; Fazekas, Franz; Ferro, José M.; Hennerici, Michael G.; Langhorne, Peter; O'Brien, John; et al. (Archives of internal medicine, 2007)
BACKGROUND: Age-related white matter changes (ARWMCs), frequently detected on neuroimaging, are associated with motor, cognitive, urinary, and mood disorders. The LADIS (LeukoAraiosis and DISability) Study primarily aims to assess ARWMCs as a determinant of global functional decline in the elderly population. - METHODS: We enrolled 639 patients (mean age, 74.1 +/- 5.0 years; 45.1% male) referred for nondisabling complaints, who had ARWMCs detected on brain magnetic resonance imaging (MRI) of mild, moderate, or severe grade according to the Fazekas scale. At the 1-year follow-up, 619 were reassessed using the Instrumental Activities of Daily Living (IADL) scale. Of these, 506 were totally independent at baseline, and 113 were impaired in only 1 item of the IADL scale. We studied the 1-year transition to 2 or more activities limited and selective functional impairments as cofactors of functional decline. - RESULTS: The rate of transition was 9%, 15%, and 26%, in the mild, moderate, and severe ARWMC group, respectively. Comparing the severe with the mild ARWMC groups and adjusting for age and for other predictors of decline, the risk was more than 2-fold higher (odds ratio; 2.38; 95% confidence interval, 1.29-4.38) in patients with 0 or 1 activity limited, and 3-fold higher (odds ratio, 3.02; 95% confidence interval, 1.34-6.78) among patients fully independent at baseline. Both motor and cognitive deterioration predominantly explained the effect of ARWMCs on global functional decline. - CONCLUSION: Elderly patients who are functionally independent and who have severe ARWMCs are at considerable risk of becoming more dependent in a short period, mostly owing to motor and cognitive deterioration.
Gesehen am 05.05.2022